Entrepreneurial Development in Renewable Energy Sector of Nepal - Yadav, Maheshwar Prasad (Nepal Journal of Multidisciplinary Research, 2022)
The paper aims at determining entrepreneurial development in renewable energy sector of Nepal. The study has adopted causal-comparative research design to determine the effect of population, number of households, number of systems installed on entrepreneurship development, i.e., renewable energy enterprises (REEs) in the context of Nepal. The required district level secondary data having 75 observations related to population, number of households, number of renewable energy enterprises, and number of renewable energy systems installed were collected for this study. Furthermore, the formation and analysis of properties of portfolios on population and number of households have been comprised to examine the relationship of district population and district households with various measures related renewable energy sector of Nepal. The analysis of portfolios thus formed is followed by the analysis of estimation of regression equations. The results show that entrepreneurship development, i.e., renewable energy enterprises (REEs) is positively related with market size in terms of populations and district households. This study is useful for renewable energy enterprises (REEs) and development actors to grow their own business and commercialization of the sector. The study can be extended by incorporating other sectors of renewable energy such as, biogas, micro-hydro, improved cooking stove, wind technology, and biomass sectors to find out greater insight into the results for the renewable energy sector.